INTERNATIONAL TRADE OF COAL IN INDIA: TRENDS, CHALLENGES AND MEASURES FOR ACHIEVING TRADE BALANCE - Ansari, Kashif; Kumar, Shiv (International Journal of Research -GRANTHAALAYAH, 2016)
Coal is one of the most important sources of electricity and energy in Indian economy. India is world’s third largest producer of coal yet it imports coal from different countries to meet its domestic requirement. With negligible amount of exports, it has resulted in trade deficit problems for Indian economy. This paper attempts to examine the burning issue of “International trade of coal in India: trends, challenges and suggestions for Improvement “from different perspectives. Accordingly the existing literature on the subject has been reviewed with topics ranging from coal exports and imports to illegal mining, clean technology and new ways to improve the quality of coal. The objective of the paper is to find reasons for huge imports and low exports of coal with a view to achieve trade balance. To conclude, it can be said that there are many unexplored areas which researchers can take up in future in order to achieve trade balance of coal.